CREDIT MANAGEMENT PRACTICES, FIRM SIZE AND FINANCIAL SUSTAINABILITY OF DEPOSIT TAKING SAVINGS AND CREDIT COOPERATIVE SOCIETIES IN KENYA - John Ndung'u GACHENGA; Dennis Kamau MUTHONI; Wilson Kipkemboi METTO (Financial Studies)
The study examined the moderating effect of firm size on the relationship between credit management practices and the financial sustainability of DT-SACCOs in Kenya. The study was grounded in information asymmetry theory, utilising a positivist paradigm and an exploratory research design. The target population consisted of 176 finance managers from 176 DT-SACCOs, providing a robust framework for analysis. The sample size was obtained using Yamane's formula, which resulted in 122 respondents, with a high response rate of 98 per cent for the structured questionnaires administered. Data was analysed using descriptive and inferential statistics. The inferential statistics revealed a strong positive association between credit management practices and financial sustainability, with p-values of 0.013. Notably, the Nagelkerke R-squared change demonstrated that firm size moderates the connection between credit management practices and financial sustainability. The study recommends enhancing financial sustainability through credit information sharing and establishing a deposit guarantee fund to protect members' funds in the event of license revocation or closure.